2019
DOI: 10.3892/etm.2019.7840
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of type 2 diabetes mellitus caveolin‑3 K15N mutation on glycometabolism

Abstract: Caveolin-3 (CAV3) is a muscle-specific protein present within the muscle cell membrane that affects signaling pathways, including the insulin signaling pathway. A previous assessment of patients with newly developed type 2 diabetes (T2DM) demonstrated that CAV3 gene mutations may lead to changes in protein secondary structure. A severe CAV3 P104L mutation has previously been indicated to influence the phosphorylation of skeletal muscle cells and result in impaired glucose metabolism. In the present study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Mice that lack caveolin-3 (cav3), a skeletal muscle-specific scaffolding protein critical in the formation of caveolae on the plasma membrane, exhibit skeletal muscle insulin resistance due to plasma membrane-specific effects on the IR (41,42). Overexpression of dominant-negative cav3 leads to decreased glucose uptake and glycogen synthesis in C2C12 cells, which is attributed to decreased Akt phosphorylation (43)(44)(45). Conversely, an increase in wildtype cav3 expression is sufficient to enhance Akt phosphorylation and glucose uptake (46).…”
Section: How Does the Inhibition Of The Lands Cycle Promote Greater Imentioning
confidence: 99%
“…Mice that lack caveolin-3 (cav3), a skeletal muscle-specific scaffolding protein critical in the formation of caveolae on the plasma membrane, exhibit skeletal muscle insulin resistance due to plasma membrane-specific effects on the IR (41,42). Overexpression of dominant-negative cav3 leads to decreased glucose uptake and glycogen synthesis in C2C12 cells, which is attributed to decreased Akt phosphorylation (43)(44)(45). Conversely, an increase in wildtype cav3 expression is sufficient to enhance Akt phosphorylation and glucose uptake (46).…”
Section: How Does the Inhibition Of The Lands Cycle Promote Greater Imentioning
confidence: 99%
“…Mice that lack caveolin-3 (cav3), a skeletal muscle-specific scaffolding protein critical in the formation of caveolae on the plasma membrane, exhibit skeletal muscle insulin resistance due to plasma membrane-specific effects on the IR (41, 42). Overexpression of dominant-negative cav3 leads to decreased glucose uptake and glycogen synthesis in C2C12 cells, which is attributed to decreased Akt phosphorylation (4345). Conversely, an increase in wildtype cav3 expression is sufficient to enhance Akt phosphorylation and glucose uptake (46).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that a variety of mutations were present in the CAV-3 gene among 1–1000 patients with T2DM. A previous assessment of patients with newly developed T2DM demonstrated that K15N muta tion located in the N-terminus of caveolin-3 may lead to changes in caveolin-3 secondary structure, thus causing decreased recombinant caveolin-3 expression [ 97 ]. It has been found that decreased expression and reduced localization of caveolin-3 by CAV-3-P104L mutation inhibited glucose uptake and glycogen synthesis [ 98 ].…”
Section: Caveolin-3 and Metabolic Perturbationmentioning
confidence: 99%